Nutrition Education and Strengthening Healthy Living Characters of Junior High School Students at Malang City - Fajar Ari Nugroho; Inggita Kusumastuty; Anggun Rindang Cempaka; Dian Handayani (FOUNDAE (Foundation of Advanced Education), 2022)
Adolescence is a period of rapid growth that a healthy lifestyle must support. School as an environment where teenagers spend most of their time has a School Health Unit (UKS), an essential part of health services at school. UKS can be used as a health education for adolescents at school. However, in reality, UKS needs to be actively used and involved. This community service healthily provided interactive education and achieved optimal growth for students through using lectures, focus group discussion, roleplay, and student projects. At the end of the activity, it was reported that there was a significant improvement in students' knowledge. This activity has also involved the role of parents and schools with UKS as part of the sustainability guarantor of healthy lifestyles for students. The provision of diverse education strategies can effectively influence students' health knowledge.